Knowledge exchange: Proceedings of the policy roundtable on ATMI-ASEAN: The case of the livestock sector in Vietnam - Southeast Asian Regional Center for Graduate Study and Research in Agriculture; International Food Policy Research Institute (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2020)
The Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA) and the International Food Policy Research Institute (IFPRI) organized the Policy Roundtable on Agricultural Transformation and Market Integration in ASEAN: The Case of the Livestock Sector in Vietnam on 15 November 2018 in Hanoi, Vietnam. The policy roundtable (PRT) was in partnership with the Institute of Policy and Strategy for Agriculture and Rural Development (IPSARD) under the project Agricultural Transformation and Market Integration in the ASEAN Region: Responding to Food Security and Inclusiveness Concerns (ATMI-ASEAN).